(untitled) (Journal of University of Babylon for Engineering Sciences, 2022)
The search for more effective and at the same time cost-effective solutions in the PV industry causes the creation of an increasing number of installations using bifacial modules. This article presents a comparison of the energy gains of two photovoltaic farms - the first with bifacial modules, and the other with mono-facial modules. Moreover, the market of bifacial modules is discussed along with development prospects in the coming years, the technologies are characterized and the main factors influencing the improvement of energy gains from the operation of panels.